Tinjauan Hasil-hasil Penelitian Faktor-faktor Alam yang Mempengaruhi Sifat Fisik dan Mekanik Kayu Indonesia Review of Researches on Natural Factors Affecting the Physical and Mechanical Properties of Indonesian Wood - Wahyu Dwianto; Sri Nugroho Marsoem (Masyarakat Peneliti Kayu Indonesia, 2008)
This review deals with several topics concerning natural factors affecting physical and mechanical properties of wood, i.e. (1) wood species; (2) age and location of growing; (3) position of wood sample in the stem; (4) diameter; (5) humidity, moisture content, and temperature; (5) weathering and fungi; (6) forest fired; that have been done by researchers who are members of Indonesian Wood Research Society. The purposes of this review are (1) to evaluate the research results that have been done, (2) to promote the applicable and feasible utilization of research results to the users, (3) to provide information concerning previous researches that might be useful for further researches.More than 60 wood species have been reported in this review. Besides the major and minor commercial wood species; lesser known species, i.e. Balsa (Ochroma spp.), Randu (Ceiba pentandra Gaertn.), Merkubung (Macaranga sp.), Cengkeh (Eugenia aromatica L.), Afrika (Maesopsis eminii), Kisereh (Cinnamomum porrectum (Roxb) Kosterm), Kibawang (Melia excelsa Jack.), Pulai Konggo (Alstonia kongoensis Engl.), Sengon Buto (Enterolobium cyclocarpum Griserb.), Salamander (Grevillea robusta A.Cunn.), Kilemo (Litsea cubeba Pers.), Tahongai (Kleinhovia hospita Linn.), Sukun (Arthocarpus altilis), Arang (Diospyros borneensis), Berumbung (Adina minutifolia), Tisuk/Waru (Hibiscus macrophyllus), Urograndis (Eucalyptus urograndis), Kelapa (Cocos nucifera L.), Kelapa Sawit (Eleais guineensiis Jacq.), Laban (Vitex Pubescens Vahl.), Rambai (Baccaurea motleyana Muell.), Ki Sampang (Evodia latifolia DC.), Nangka (Artocarpus integra Merr.), Kalapi (Kalappia celebica), Gofasa (Vitex coffasus), Ketileng (Vitex glabrata), Cemara (Gymnostoma sp.), and Lamtoro (Leucaena glauca (Willd) Benth). have also been observed. The researches were generally done in relation to the utilization prospect of lesser known species, crops estate species, fast growing species, timber estate species, rural forest species, commercial species, for contruction/structural materials, handy-craft, musical instruments, or out-door exposures.Wood properties were interaction between specific gravity or density, moisture content, shrinkage and mechanical properties of wood. However, the values of those physical and mechanical properties in the papers could not directly compared to each other, because there were various testing standard and strength classification used. And unfortunately, researches on acoustic, thermal, electrical, creep, relaxation, and fatigue behaviour of Indonesian wood species were very rare or almost none.